1994
DOI: 10.1136/bjsm.28.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Resistance exercise decreases beta-endorphin immunoreactivity.

Abstract: Previous research investigating the response of plasma P-endorphins to resistance exercise has resulted in equivocal findings. To examine further the effects of resistance exercise on 3-EP immunoreactivity, 10 male and 10 female college-age students participated in a series of controlled isotonic resistance exercises. The session consisted of three sets of eight repetitions at 80% of one repetition maximum (1-RM) for each of the following exercises: (1) bench press; (2) lateral pull-downs; (3) seated arm curl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
(2 reference statements)
0
8
0
1
Order By: Relevance
“…More detailed investigations revealed that an anaerobic state, which was reached at a threshold of about 90 % of maximum oxygen consumption and was documented by a blood lactate level of more than 4 mmol/l arterialized blood, leads to a considerable increase of β-endorphin levels in human plasma under exercise [24,26]. Compatible with these findings was the fact that non-exhaustive performance such as heavy resistance exercise, although requiring high muscular activity for short time periods, did not lead to an increase of β-endorphin levels at all [20], even decreased them [21], or only allowed an increase under approximately exhaustive conditions [14]. On the other hand, one would have expected an enhancement of exhaustive exercise-induced β-endorphin release under additional hypoxia which, however, was not observed [5,13].…”
Section: Discussionmentioning
confidence: 98%
“…More detailed investigations revealed that an anaerobic state, which was reached at a threshold of about 90 % of maximum oxygen consumption and was documented by a blood lactate level of more than 4 mmol/l arterialized blood, leads to a considerable increase of β-endorphin levels in human plasma under exercise [24,26]. Compatible with these findings was the fact that non-exhaustive performance such as heavy resistance exercise, although requiring high muscular activity for short time periods, did not lead to an increase of β-endorphin levels at all [20], even decreased them [21], or only allowed an increase under approximately exhaustive conditions [14]. On the other hand, one would have expected an enhancement of exhaustive exercise-induced β-endorphin release under additional hypoxia which, however, was not observed [5,13].…”
Section: Discussionmentioning
confidence: 98%
“…However, the endorphin hypothesis has been mainly supported only in participants who engage in cardiovascular exercise 28,29 compared to resistance training. 30 In this present study, a greater number of females (n = 37) participated in cardiovascular only exercise compared to males (n = 6). Meanwhile, more males (n = 60) participated in resistance (weight training) only exercise compared to women (n = 7).…”
Section: Discussionmentioning
confidence: 72%
“…(61) reportaram que não havia alterações significativas nos níveis de -end 1-31 em seis homens treinados, após a execução de três séries de oito repetições, a 80% da repetição máxima (1 RM). Em contraste, esses mesmos autores depois verificaram que os níveis de -end 1-31 diminuíam significativamente após a realização de um protocolo similar de exercício de força aplicado em estudantes (63). Outro estudo, em que sete homens treinados executaram um protocolo de três séries de 10 RM com quatro exercícios diferentes, demonstrou que um baixo volume de exercício de força não aumenta significativamente os níveis de -end (62).…”
Section: Respostas Da -End 1-31 Induzidas Pelo Exercício De Forçaunclassified